Development of a functional rehabilitation intervention for post knee arthroplasty patients: COmmunity based Rehabilitation post Knee Arthroplasty (CORKA) trial - Room, J; Batting, M; Barker, KL (Elsevier, 2019)
Knee osteoarthritis is a common cause of disability in older people and knee arthroplasty surgery in the UK is increasing. The CORKA trial is a randomised controlled trial of rehabilitation targeted at patients identified as being at risk of a poor outcome after knee arthroplasty. This paper describes the development and delivery of the CORKA intervention. It was informed by current evidence, relevant guidelines, expert and patient opinion, practical considerations and a pilot study. The intervention is a multicomponent rehabilitation programme with the main component being an exercise programme delivered to participants in their own home. It includes functional task practice, strategies to improve adherence and where appropriate the provision of appropriate aids and equipment.